Quality of life of workers in a long stay institution for the elderly: scoping review (Research, Society and Development, 2021)
Objective: to analyze the factors that influence the quality of life of workers in long-stay institutions for the elderly. Methods: scope review with selection of articles on the subject in the SciELO, Pubmed and CINAHL databases, from August to October 2020. Studies with workers from long-stay institutions for the elderly were included. For data analysis, an Excel instrument was used to categorize and better visualize the essential elements report. Results: according to the search in the databases, 143 articles were found, including 8 articles. Data were classified into three categories: characterization of workers, factors that influence the quality of life of workers in a long-term care institution for the elderly, and coping strategies. Conclusion: it is concluded that this research is relevant and contributes to both the worker and the elderly in long-stay institutions, at a time when it will bring a look at the demands and difficulties encountered in their professional practice.